(untitled) (Journal of Engineering, 2008)
This paper studies the two-dimensional analysis of the consolidation process for partially saturated soils applied to an earth embankment mainly from the theoretical point of view. The method of finite elements is used to find a numerical solution to describe the behavior of soils during consolidation. Moreover, this study was carried for both, isothermal and non-isothermal cases. The case of two–dimensional, plane strain consolidation is considered, as it is widely needed in the studies of soil mechanics. The parameters studied are displacement in the y–direction, pore water pressure, pore air pressure, and temperature. The embankment was constructed in Basrah - Iraq, where the temperature is usually high at most days of the year. It is believed that it is more realistic to model the embankment as a partially saturated soil rather than a fully saturated soil as was done before. The study reveals that: – - The consolidation process is affected by the degree of saturation. As the paths in the soil that are used by the pore–water and/or the pore–air may transfer from one state (open path) to another state (closed path) and vice versa. - The pore–water and the pore–air pressures are affected by temperature. The pressure increases when the temperature increases (for a constant volume). This is usually the case inside the partially saturated soil. Temperature can affect indirectly the soil skeleton as a result of the change in pore–air and pore–water pressures. - The vertical displacement for partially saturated soil consolidation under self weight loading is noticed to have almost regular settlement. Then, there is an accelerated settlement due to the dissipation of the air and water pressures. After a while (after excess pressures dissipation), there will be a classical consolidation form.